Using Insect Monitoring and Economic Threshold as Decision Tools in Sweet Corn Pest Management - Nawanich, Sangkhae; Chongrattanameteekul, Wiboon (Agriculture and Natural Resources, 2014)
Farmers must use insecticides when growing sweet corn to protect their crops from damage by insect pests. However, such practice has caused many serious consequences. One of the long term solutions is to implement insect monitoring for decision making and to apply insecticide only when the pest population reaches a certain threshold. The reduced application of insecticide will help to conserve predators and parasitoids. This research focused on the implementation of insect monitoring and the economic threshold in sweet corn pest management. The experiment was conducted at the National Corn and Sorghum Research Center (Suwan Farm), Pakchong, Nakhon Ratchasima province, Thailand during November 2010–February 2011 by comparing two treatments. The ﬁ rst treatment involved partial weed control with emphasis on maintaining some of the weed population to serve as the nectar source and habitat for the natural enemies of insect pests together with regular ﬁ eld monitoring to obtain information for decision making and applying insecticide only when the pest population reached the speciﬁ ed economic threshold. The second treatment was complete weed control and calendar spraying of insecticide. The results showed that plots with the ﬁ rst treatment produced an average beneﬁ t of USD 4,205 ha-1while that of the second treatment was USD 3,845 ha-1. Although the numbers of key pests and the level of crop damage from both treatments were signiﬁ cantly different, the levels were lower than the economic threshold. However, the numbers of natural enemies from the ﬁ rst treatment were much higher than those from the second treatment. The three major groups of natural enemies observed were Arachnids, Chelisochidae and Anthocoridae (Orius sp.). Therefore, regular ﬁ eld surveys before making a decision to apply insecticide should be promoted among sweet corn growers to reduce the amount of chemical applied which should achieve a reduction in the production costs and the hazards to farmers, consumers and the environment.